Annual Plan 2009-10 Volume-I Planning, Programme Monitoring and Statistics Department January 2009 - Planning Commission (Planning Commission, 2009)
The outlay for the Tenth Five Year Plan was Rs.43558 crores at 2001-02 prices which was 86% more than the Ninth Five Year Plan outlay of Rs. 23400 crores. The approved Annual Plan outlays in the Tenth Five Year Plan and expenditure are shown in the statement below. It may be seen that Karnataka has been stepping up the outlays at an annual average of 14% in the Tenth Five Year Plan while the expenditure has matched the outlays with an annual average increase of 15%.
Planning, Programme Monitoring and Statistics Department
Planning, Programme Monitoring and Statistics Department